ANALISIS KOHESI PADA PIDATO BARRACK OBAMA DI UNIVERSITAS INDONESIA - TAMAHEANG, NOLA (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2017)
ABSTRACT The title of this research is Cohesive Analysis of Barrack Obama’s Speech at the University Of Indonesia. It is an attempt to analyze and explain the cohesive items in Barrack Obama speech. This research is expected to help students or readers in understanding the using of grammatical cohesive in text of speech. The objectives of this research are to identify, classify, and analyse descriptively the aspects of grammatical cohesion  on the text of  Barrack Obama’s speech at the University of Indonesia. The theory  used  in this research is taken from a book called the Perspective of Discourse Analysis: Theory and Practice by Alba-Juez (2009), which states that one of those criteria which can be used to analyse the  discourse is the aspects of cohesion. And the theory was supported this research is taken  from Halliday and Hasan (1976). The theory focused on the aspects of  grammatical cohesion. The grammatical cohesion is used to link the elements of a text, namely pronoun, substitution, ellipsis, and conjunction.  The text of speech is taken from the internet. The result shows that this speech contains the four types grammatical aspects of cohesion as suggested by Alba-Juez(2009). There are 34 paragraphs which contain the grammatical aspects of cohesion.The most gramatical  cohesive  used was Pronouns and conjunction.    Keywords : Aspects of Cohesion, Grammatical Cohesion, Barrack Obama’s Speech